Susceptibility to extinction and reinstatement of ethanol-induced conditioned place preference is related to differences in astrocyte cystine-glutamate antiporter content - Amaral, Vanessa Cristiane Santana [UNESP]; Morais-Silva, Gessynger [UNESP]; Laverde, Celina F. [UNESP]; Marin, Marcelo T. [UNESP] (Elsevier, 2020)
Individual susceptibility to alcohol effects plays an important role in the development of alcohol addiction and studies have shown that glutamate release is altered after chronic ethanol consumption. The cystine-glutamate antiporter (xCT) is a protein that regulates glutamate release. However, little is known about the relationship between xCT levels and this individual susceptibility. Thus, this study aimed to evaluate the relationship between the extinction and stress-induced reinstatement of ethanol conditioned place preference (CPP) and xCT levels in the medial prefrontal cortex (mPFC), nucleus accumbens (NAcc) and amygdala (Amy). Male Swiss mice were submitted to a CPP procedure followed by an extinction protocol and then identified as those which extinguished the CPP and those that did not. In another cohort, mice that extinguished the CPP were submitted to a protocol of stress-induced reinstatement. Immediately after the tests, brains were removed for xCT quantification. The xCT levels were significantly lower in the mPFC and NAcc of mice that did not extinguish CPP. Moreover, mice that were susceptible to stress-induced reinstatement of CPP had lower levels of xCT in the NAcc. Our results suggest that individual susceptibility to the extinction and reinstatement of ethanol CPP is related to alterations in xCT levels.
Keywords: Conditioned place preference; Cystine-glutamate antiporter; Ethanol; Medial prefrontal cortex; Nucleus accumbens; Reinstatement